2009
DOI: 10.1080/03639040802698802
|View full text |Cite
|
Sign up to set email alerts
|

Generic omeprazole delayed-release capsules: in vitro performance evaluations

Abstract: There is no scientific evidence to support the claims that the generic omeprazole delayed-release capsules perform differently from the brand omeprazole product in vitro.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 2 publications
0
11
0
Order By: Relevance
“…9 However, it should be noted that in a study evaluating 5 generic omeprazole products in the United States, all 5 products met the in vitro drug dissolution standards established by the United States Pharmacopeia. 10 In this study, we evaluated the use of a 10 mg omeprazole capsule from a single source Adverse GI effects are frequently reported in dogs after PPI administration, with the most common reported adverse events being vomiting and diarrhea. 4,5,11 Vomiting was limited to 3 episodes in 2 dogs receiving omeprazole.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 However, it should be noted that in a study evaluating 5 generic omeprazole products in the United States, all 5 products met the in vitro drug dissolution standards established by the United States Pharmacopeia. 10 In this study, we evaluated the use of a 10 mg omeprazole capsule from a single source Adverse GI effects are frequently reported in dogs after PPI administration, with the most common reported adverse events being vomiting and diarrhea. 4,5,11 Vomiting was limited to 3 episodes in 2 dogs receiving omeprazole.…”
Section: Discussionmentioning
confidence: 99%
“…In other countries such as Cambodia, generic omeprazole formulations have been demonstrated to vary widely because of the use of cheaper coating substitutes and, consequently, premature release of the drug in the stomach 9 . However, it should be noted that in a study evaluating 5 generic omeprazole products in the United States, all 5 products met the in vitro drug dissolution standards established by the United States Pharmacopeia 10 . In this study, we evaluated the use of a 10 mg omeprazole capsule from a single source (TriviumVet) undergoing FDA approval for use in dogs to explore 0.5 to 1.0 mg/kg tailored dosing and to evaluate the efficacy of the product in increasing gastric pH in dogs.…”
Section: Discussionmentioning
confidence: 99%
“…In accordance to the pharmacopoeia, in-vitro drug release from enteric-coated formulations should be tested in two stages at two different pH which is intended to mimic the pH in the stomach ("gastric phase") and intestinal environment ("intestinal phase") (29). For the testing of delayed-release omeprazole pellets in the "gastric phase", 500-1000ml of 0.1N solution of hydrochloric acid with pH 1.2 as dissolution media and Apparatus I or II at the rotation speed 50-100rpm for 2 h are usually used (1,20,30,31). In accordance with the pharmacopoeia, phosphate buffer solution with a pH of 6.8 should be used during the dissolution test to mimic the intestinal environment (31).…”
Section: Dissolution Test and Acid Resistance Of Commercial Delayed-r...mentioning
confidence: 99%
“…For the testing of delayed-release omeprazole pellets in the "gastric phase", 500-1000ml of 0.1N solution of hydrochloric acid with pH 1.2 as dissolution media and Apparatus I or II at the rotation speed 50-100rpm for 2 h are usually used (1,20,30,31). In accordance with the pharmacopoeia, phosphate buffer solution with a pH of 6.8 should be used during the dissolution test to mimic the intestinal environment (31). Previously it has been shown that the dissolution of omeprazole at pH 6.5 is not reliable and can lead to incorrect conclusions because of the short omeprazole half-life at this pH, while phosphate buffer with pH 7.4 gave reproducible and discriminative results (20).…”
Section: Dissolution Test and Acid Resistance Of Commercial Delayed-r...mentioning
confidence: 99%
“…Interestingly, in contrast to the omeprazole products marketed outside the US which may differ in their enteric coating design characteristics, the omeprazole products approved in the US are similarly designed to the RLD to provide comparable protection against acid degradation through pH 5-5.5 (8). It appears, in this instance, that although this was not considered as a precondition for ANDA approval, the US generic manufactures may have been aware of the critical importance of having within their product design, an enteric coating that provides similar protection as the RLD to ensure therapeutic equivalence.…”
Section: Modified-release Drug Products: Impact Of the Active Ingredimentioning
confidence: 95%